Modulation of Drosophila heat shock transcription factor activity by the molecular chaperone DROJ1 - Marchler, Gabriele (Oxford University Press, 2001)
Heat shock transcription factors (HSFs) play important roles in the cellular response to physiological stress signals. To examine the control of HSF activity, we undertook a yeast two-hybrid screen for proteins interacting with Drosophila HSF. DROJ1, the fly counterpart of the human heat shock protein HSP40/HDJ1, was identified as the dominant interacting protein (15 independent isolates from 58 candidates). Overexpression of DROJ1 in Drosophila SL2 cells delays the onset of the heat shock response. Moreover, RNA interference involving transfection of SL2 cells with double-stranded droj1 RNA depletes the endogenous level of DROJ1 protein, leading to constitutive activation of endogenous heat shock genes. The induction level, modest when DROJ1 was depleted alone, reached maximal levels when DROJ1 and HSP70/HSC70, or DROJ1 and HSP90, were depleted concurrently. Chaperone co-depletion was also correlated with strong induction of the DNA binding activity of HSF. Our findings support a model in which synergistic interactions between DROJ1 and the HSP70/HSC70 and HSP90 chaperones modulate HSF activity by feedback repression.